Genome-wide significance for a modifier of age at neurological onset in Huntington's Disease at 6q23-24: the HD MAPS study - Gillis Tammy; Mysore Jayalakshmi; Djoussé Luc; Xu Gang; Prakash Ranjana; Wheeler Vanessa C; Lazzarini Alice; Ashizawa Tetsuo; Jones Randi; Paulsen Jane S; Frontali Marina; Novelletto Andrea; et al. (BMC, 2006)
Abstract Background Age at onset of Huntington's disease (HD) is correlated with the size of the abnormal CAG repeat expansion in the HD gene; however, several studies have indicated that other genetic factors also contribute to the variability in HD age at onset. To identify modifier genes, we recently reported a whole-genome scan in a sample of 629 affected sibling pairs from 295 pedigrees, in which six genomic regions provided suggestive evidence for quantitative trait loci (QTL), modifying age at onset in HD. Methods In order to test the replication of this finding, eighteen microsatellite markers, three from each of the six genomic regions, were genotyped in 102 newly recruited sibling pairs from 69 pedigrees, and data were analyzed, using a multipoint linkage variance component method, in the follow-up sample and the combined sample of 352 pedigrees with 753 sibling pairs. Results Suggestive evidence for linkage at 6q23-24 in the follow-up sample (LOD = 1.87, p = 0.002) increased to genome-wide significance for linkage in the combined sample (LOD = 4.05, p = 0.00001), while suggestive evidence for linkage was observed at 18q22, in both the follow-up sample (LOD = 0.79, p = 0.03) and the combined sample (LOD = 1.78, p = 0.002). Epistatic analysis indicated that there is no interaction between 6q23-24 and other loci. Conclusion In this replication study, linkage for modifier of age at onset in HD was confirmed at 6q23-24. Evidence for linkage was also found at 18q22. The demonstration of statistically significant linkage to a potential modifier locus opens the path to location cloning of a gene capable of altering HD pathogenesis, which could provide a validated target for therapeutic development in the human patient.